Exogenous Abscisic Acid Priming Modulates Water Relation Responses of Two Tomato Genotypes With Contrasting Endogenous Abscisic Acid Levels to Progressive Soil Drying Under Elevated CO2 - Li, Shenglan; Liu, Fulai (Frontiers in Plant Science, 2021)
Plants have evolved multiple strategies to survive and adapt when confronting the changing climate, including elevated CO2 concentration (e[CO2]) and intensified drought stress. To explore the role of ABA in modulating the response of plant water relation characteristics to progressive drought under ambient (a[CO2], 400 ppm) and e[CO2] (800 ppm) growth environments, two tomato (Solanum lycopersicum) genotypes, Ailsa Craig (AC) and its ABA-deficient mutant (flacca), were grown in pots, treated with or without exogenous ABA, and exposed to progressive soil drying until all plant available water in the pot was depleted. The results showed that exogenous ABA application improved leaf water potential, osmotic potential and leaf turgor, and increased leaf ABA concentrations ([ABA]leaf) in AC and flacca. In both genotypes, exogenous ABA application decreased stomatal pore aperture and stomatal conductance (gs), though these effects were less pronounced in e[CO2]-grown AC and gs of ABA-treated flacca was gradually increased until a soil water threshold after which gs started to decline. In addition, ABA-treated flacca showed a partly restored stomatal drought response even when the accumulation of [ABA]leaf was vanished, implying [ABA]leaf might be not directly responsible for the decreased gs. During soil drying, [ABA]leaf remained higher in e[CO2]-grown plants compared with those under a[CO2], and a high xylem sap ABA concentration was also noticed in the ABA-treated flacca especially under e[CO2], suggesting that e[CO2] might exert an effect on ABA degradation and/or redistribution. Collectively, a fine-tune ABA homeostasis under combined e[CO2] and drought stress allowed plants to optimize leaf gas exchange and plant water relations, yet more detailed research regarding ABA metabolism are still needed to fully explore the role of ABA in mediating plant physiological response to future drier and CO2-enriched climate.